Breakfast Eater vs Breakfast Skipper (Who is better on Cognitive Function): A Correlational Study among College Students - Siti Maryam; Fadli Agani; Fatmawati Fatmawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2021)
Breakfast is one of the most important meals within a day and many studies have found that regular breakfast consumption is important in order to maintain an academic performance above average. However, young adults aged 17-24 years old are the highest population of breakfast skippers among other groups. Therefore, this study aimed to measure the association between frequency of breakfast consumption and cognitive function among college students in Banda Aceh city. The number of participant recruited through simple random technique was 300 college students. Cognitive Functioning Self-Assessment Scale was employed in order to obtain the data on cognitive function, whereas breakfast consumption was calculated based on the frequency of taking breakfast during the past week. Pearson Correlation was used to analyze the data and it showed a positive relationship between those two variables. Besides, the analysis also displayed a significance value of 0.000 (p<0.05). This indicated that the hypothesis was accepted –there was a very significant relationship between frequency of breakfast consumption and cognitive function among college students in Banda Aceh city.